Temperature stability of a pure metakaolin based K‐geopolymer: Part 1. Variations in the amorphous mineral network. Issue 10 (22nd June 2020) - Gomes, Sandrine; Petit, Elodie; Frezet, Lawrence; Thirouard, Rodolphe; Taviot‐Gueho, Christine; Gharzouni, Ameni; Rossignol, Sylvie; Renaudin, Guillaume
Abstract: The thermal behavior of a model MK based K‐geopolymer (Si/Al = 1.38 and K/Al = 0.68; obtained by alkaline activation of a very pure metakaolin) was investigated between room temperature and 1400°C in order to evaluate its potentiality for high‐temperature applications. The purpose of our study was to monitor the behavior of a geopolymer during a temperature rise in order to better understand its variations with respect to temperature. The works from the present paper focus only variations in the internal structure of the mineral matrix. The results presented here show that the amorphous mineral matrix is preserved up to 900°C. The results also show that there is a densification of the internal structure of tetrahedral network during heating, due to changes in the Q 3 environments in fully‐connected Q 4 for both silicates and aluminates. Thus, our work provides a new more precise vision of the 3D geopolymeric mineral matrix for which the silicoaluminous network is not exclusively composed of Q 4 entities, contrary to what is frequently encountered in the literature before.